Research Seminar on Non-Biblical Scriptures - Amalorpavadass, D. S. (National Biblical, Catechetical and Liturgical Centre, 1974)
Comparative study of Christianity, Hinduism, and Islam; comprises papers of a seminar organized by National Biblical, Catechetical, and Liturgial Centre, Bangalor.